The Influence of Local Wisdom and Culture Approach Strategy on CSR Implementation in Klayas Village - Dody Yapsenang; Utami, Dyah Putri; Bambang Imawan; Abidin; Pratama Bimo (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
Klayas Village is one of the daerah terpencils in the Seget District which is the Ring 1 area of ​​Company X. Most of the Klayas community is the Moi Tribe indigenous people who make their living from the sago forest. Since its establishment in 1997, Company X has actively and routinely carried out charity-based CSR activities in Klayas Village. Since 2019, the CSR program of Company X has changed in concept from Charity to a sustainable CSR program which consists of various activities. The people of Klayas Village have difficulty adapting to the new CSR scheme, resulting in resistance. In addition, the implemented program is not in accordance with community habits. In response to this rejection, in 2020, Company X implemented a strategy of approaching local wisdom and traditional culture of the Moi Tribe to increase community enthusiasm. This has proven to be more effective in increasing community participation. It can be seen from the programs implemented in 2020 that are still relevant and sustainable until 2022. The number of beneficiaries is much larger and more comprehensive. This strategy can also increase cohesiveness between the company-community and between members of the community itself.